Price Competition in Product Variety Networks - Philip Ushchev; Yves Zenou (Fondazione Eni Enrico Mattei (FEEM), 2016)
We develop a product-differentiated model where the product space is a network defined as a set of varieties (nodes) linked by their degrees of substitutability (edges). We also locate consumers into this network, so that the location of each consumer (node) corresponds to her “ideal” variety. We show that, even though prices need not to be strategic complements, there exists a unique Nash equilibrium in the price game among firms. Equilibrium prices are determined by both firms' sign-alternating Bonacich centralities and the average willingness to pay across consumers. They both hinge on the network structure of the firm-product space. We also investigate how local product differentiation and the spatial discount factor affect the equilibrium prices. We show that these effects non-trivially depend on the network structure. In particular, we find that, in a star-shaped network, the firm located in the star node does not always enjoy higher monopoly power than the peripheral firms.
Keywords: D43; L11; L13; 330; Networks; Product Variety; Monopolistic Competition; Spatial Competition